Asymptotically Stable Solutions of a Generalized Fractional Quadratic Functional-Integral Equation of Erdélyi-Kober Type - Mohamed Abdalla Darwish; Beata Rzepka (Journal of Function Spaces)
We study a generalized fractional quadratic functional-integral equation of Erdélyi-Kober type in the Banach space BC(ℝ+). We show that this equation has at least one asymptotically stable solution.